2016
DOI: 10.4103/2230-8210.192916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curative parathyroidectomy on insulin resistance

Abstract: Background:Primary hyperparathyroidism (PHPT) is characterized by inappropriately elevated serum parathyroid hormone (PTH) level despite elevated serum calcium. Insulin resistant is the basic pathophysiology, behind the higher prevalence of diabetes mellitus in patients with PHPT. However, the improvement in insulin resistance (IR) after curative parathyroidectomy (CPTX) has not been established yet, as the study results are conflicting.Materials and Methods:In this prospective interventional study, ten patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
1
3
0
1
Order By: Relevance
“…[ 14 15 ] Our study is not in agreement with the results of other Indian studies where majority of patients were <40 years of age. [ 16 17 18 ] In one study from Kashmir, the mean age of patients at presentation was 44.72 ± 12.46 years which matches with our data probably because 62% of patients in that study were enrolled after 2012. [ 19 ] The reason why PHPT presents at a younger age in our country is possibly because of the associated Vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 83%
“…[ 14 15 ] Our study is not in agreement with the results of other Indian studies where majority of patients were <40 years of age. [ 16 17 18 ] In one study from Kashmir, the mean age of patients at presentation was 44.72 ± 12.46 years which matches with our data probably because 62% of patients in that study were enrolled after 2012. [ 19 ] The reason why PHPT presents at a younger age in our country is possibly because of the associated Vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, evidence for the beneficial effect of PTX in mild PHPT is scarce ( 13 ). In single arm studies following patients after PTX, a trend toward an increase of insulin resistance (HOMA-IR and QUICKI) was found in a single recent study ( 32 ), while another study found some improvement in glucose metabolism in non-diabetic patients ( 25 ). The present randomized, controlled study did not indicate a longitudinal change or between-group difference in the markers of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 92%
“…PTx improved glucose metabolism in PHPT patients after 6 months (28, 33, 53, 54) or 12 months (55), while other studies did not report such an improvement (56,57). Considering mild PHPT patients, an increased insulin resistance (HOMA IR) and lower quantitative insulin sensitivity check index (QUICKI) compared to controls, has been reported by some investigators (54); however, these findings were not confirmed by Gianotti et al (56).…”
Section: Glucose Metabolismmentioning
confidence: 91%
“…Considering mild PHPT patients, an increased insulin resistance (HOMA IR) and lower quantitative insulin sensitivity check index (QUICKI) compared to controls, has been reported by some investigators (54); however, these findings were not confirmed by Gianotti et al (56). PTx in patients with mild PHPT showed no improvement in insulin sensitivity after one year (57,58,59) or 2 years (41). In patients with asymptomatic PHPT, a conservative follow-up of 18 months showed no progression of calcium and glucose metabolism abnormalities (60).…”
Section: Glucose Metabolismmentioning
confidence: 93%